Towards Explaining Knowledge Hiding through Relationship Conflict, Frustration, and Irritability: The Case of Public Sector Teaching Hospitals - Tahira Alam (MDPI AG, 2021)
Organizations grow and excel with knowledge sharing; on the other hand, knowledge hiding is a negative behavior that impedes innovation, growth, problem solving, and timely correct decision making in organizations. It becomes more critical in the case of teaching hospitals, where, besides patient care, medical students are taught and trained. We assume that negative emotions lead employees to hide explicit knowledge, and in the same vein, this study has attempted to explain the hiding of explicit knowledge in the presence of relational conflicts, frustration, and irritability. We collected data from 290 employees of a public sector healthcare organization on adopted scales to test conjectured relationships among selected variables. Statistical treatments were applied to determine the quality of the data and inferential statistics were used to test hypotheses. The findings reveal that relationship conflicts positively affect knowledge hiding, and frustration partially mediates the relationship between relationship conflicts and knowledge hiding. Irritability moderates the relationship between relationship conflicts and frustration. The findings have both theoretical and empirical implications. Theoretically, the study tests a novel combination of variables, and adds details regarding the intensity of their relationships to the existing body of literature. Practically, the study guides hospital administrators in managing knowledge hiding, and informs on how to maintain it at the lowest possible level.